Avaliação de laboratórios de análise de solo, e da fertilidade do solo de lavouras cafeeiras em produção, na região sul de Minas Gerais. - Figueiredo, Vanessa Castro (2010)
The greatest cultivation notability in the South of Minas Gerais is the cultivation of coffee, and the soil fertility is one of the main factors that can limit the cultivation production. The purpose of this work was to evaluate soil analysis lab in the South of Minas Gerais in relation to structure and verify the soil fertility conditions in areas occupied by coffee crops that are producing in the South of Minas Gerais. A collection of facts of all soil analysis labs in the South of Minas Gerais was made and a questionary previously prepared containing 31 questions was sent to whom was responsible for those labs. After those questionaries were filled out, a lab was selected and from this one we had 2547 results it was selected 2406 soil analysis results referring to the superficial layer (0 20 cm) of areas occupied by coffee crops that were producing, located in the South of Minas Gerais and from those results, it was made the evaluation of the soil fertility of those areas. It was concluded that the majority of the labs of soil analysis located in the South of Minas Gerais present adequate conditions to the evaluation of the soil fertility. And the available P, the pH and the saturation based on the attribute of fertility that can bi in worse conditions than the occupied areas by coffee crops that are producing, located in the South of Minas Gerais.